Process for producing metal magnetic powder core APC gas atomization Fe-Si-Al

Fe-Si-Al powder was prepared by aerosolization and insulating coating was carried out by phosphoric acid passivation and aluminum ion hydrolysis. Combined with heat treatment and molding technology, the problem of poor strength of aerosolized iron-silicon aluminum soft magnetic powder core was solved, and the resistivity and saturation resistance of the powder core were improved on the basis of maintaining excellent magnetic properties.

CN119681262APending Publication Date: 2025-03-25HUIZHOU ANKEYUAN MAGNETIC DEVICES CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411784284.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The structural strength of the existing aerosolized iron-silicon aluminum soft magnetic powder core is poor, and it is difficult to effectively improve its strength while maintaining excellent magnetic properties.

Method used

Fe-Si-Al powder was prepared by aerosolization process, and insulating coating was carried out through phosphoric acid passivation and aluminum ion hydrolysis. Combined with heat treatment and molding, alumina-covered Fe-Si-Al powder core was formed.

Benefits of technology

Under medium and high frequency and high Bm conditions, the resistivity of the powder core is improved, the magnetic loss is reduced, and the anti-saturation performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a metal magnetic powder core APC gas atomization Fe-Si-Al production process, and belongs to the technical field of metal soft magnetic materials, the metal magnetic powder core APC gas atomization Fe-Si-Al production process comprises the following steps: firstly, preparing Fe-Si-A1 powder with the particle size D50 of 5 microns, Fe-Si-A1 powder with the particle size D50 of 35 microns and Fe-Si-A1 powder with the particle size D50 of 90 microns through a gas atomization method; the Fe-Si-A1 powder with the small particle size is passivated through phosphoric acid; then, A1 (OH) 3 is prepared through an aluminum ion hydrolysis method so as to preliminarily coat the magnetic powder, most of A1 (OH) 3 on the surface layer of the magnetic powder is decomposed into aluminum oxide through heat treatment, and therefore the purpose of insulation coating is achieved; and finally, carrying out compression molding on the magnetic powder core. The metal magnetic powder core APC gas atomization Fe-Si-Al production process solves the technical problem of how to improve the soft magnetic performance of a gas atomization Fe-Si-Al soft magnetic powder core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal soft magnetic materials, in particular to a production process of metal magnetic powder core APC gas atomization sendust. Background Art

[0002] Magnetic materials refer to materials that can directly or indirectly generate magnetism from Fe, Co, Ni and their alloys. As a basic metal functional material, it is widely used in various fields such as energy, electronic communications, mechanical engineering, etc., especially in the field of information technology. Magnetic materials can be mainly divided into soft magnetic materials and permanent magnetic materials; among them, materials that are easily magnetized to saturation and easily demagnetized under the action of an external magnetic field are called soft magnetic materials. Soft magnetic materials are mainly divided into three categories according to the application frequency: the first is metal soft magnetic materials used in the industrial frequency range, the second is soft magnetic composite materials used in kilohertz to megahertz, and the third is soft magnetic ferrite materials used in megahertz to gigahertz.

[0003] Metallic soft magnetic materials mainly include electrical pure iron, F-Si, Fe-Ni-(Mo), Fe-Al, Fe-Si-Al, Fe-Co alloys, etc. They have high saturation magnetization and magnetic permeability and can be widely used in transformers, sensors and other electronic power industries. In the manufacturing process of metallic soft magnetic materials, pure iron powder cores can be divided into water-atomized iron powder cores and carbonyl powder cores according to the different base powders. The water-atomized iron powder core is made of water-atomized iron powder as raw material, and the surface is pressed after insulation coating. It has low cost, high saturation magnetic induction and low coercive force, and can realize the miniaturization of high-power devices, but the resistivity is low, and the eddy current loss is large under medium and high frequency conditions. It is often used in high-power, low-frequency electronic components, such as energy storage inductors, filters and transformers. Carbonyl powder cores are pressed with ultra-pure and ultra-fine carbonyl iron powder, have good DC bias characteristics, and relatively low eddy current loss under medium and high frequencies. They are often used to prepare inductors, chokes, etc., but their density is relatively low.

[0004] Based on this, Chinese patent CN109317688B discloses a method for preparing gas-atomized iron-silicon-aluminum powder, which includes the following steps: using two smelting furnaces to melt iron-silicon alloy and aluminum respectively, and using nitrogen to protect the smelting furnace mouths; pouring the iron-silicon alloy melt and the aluminum melt into a tundish together, entering the gas atomization chamber through the nozzle at the bottom of the tundish, and using high-pressure nitrogen to atomize the mixed melt into droplets, and after the droplets are cooled, iron-silicon-aluminum powder is obtained. This method can overcome the major obstacle that the gas atomization process cannot be carried out due to the different melting points of iron-silicon-aluminum under non-vacuum conditions, which causes low-melting-point aluminum to produce oxidation slag to block the nozzle, so that the gas atomization process can still proceed smoothly in the non-vacuum state, and the performance of the obtained iron-silicon-aluminum powder can meet customer needs, the metal actual recovery rate is high, industrial production can be realized under non-vacuum conditions, the operation is simple, the production efficiency is high, the equipment cost is greatly reduced, the maintenance is convenient, and the product performance is excellent.

[0005] Furthermore, another Chinese patent CN109285685B also discloses a method for preparing a high magnetic permeability atomized Sendust magnetic powder core. The preparation method comprises: atomization powder making; particle size combination; powder heat treatment; insulation coating; secondary coating; pressing and forming; magnetic core annealing; impregnation spraying. The atomized Sendust magnetic powder core prepared by this method has the advantages of good formability and high magnetic permeability.

[0006] However, the aerosolized sendust magnetic powder core disclosed above still has the technical problem of poor structural strength. Specifically, insulation coating is a crucial preparation process in the preparation of metal soft magnetic powder cores, and the quality of the insulation coating is closely related to the magnetic performance parameters of the magnetic powder core, such as the effective magnetic permeability, DC bias performance, and loss. The thinner the insulation layer, the more uniform the coating, and the higher the resistivity of the insulation layer, the more conducive it is to obtain a soft magnetic powder core with excellent magnetic properties. However, among the various soft magnetic powder core manufacturing methods disclosed in existing patents, most of them adopt a single organic or inorganic insulation coating method. These methods are difficult to effectively solve the technical problem of poor strength of aerosolized sendust soft magnetic powder cores while maintaining excellent magnetic properties. Summary of the invention

[0007] Based on this, it is necessary to provide a metal magnetic powder core APC aerosolized sendustine production process to address the technical problem of how to improve the soft magnetic properties of the aerosolized sendustine soft magnetic powder core.

[0008] A metal magnetic powder core APC gas atomization iron silicon aluminum production process, comprising the following steps: S1: preparing Fe-Si-Al powder with a preset particle size by gas atomization process; S2: Prepare buffer solution, weigh a preset amount of Na2CO3 and deionized water, place in a container and mix and stir until the solution is clear; S3: Prepare an aluminum source solution, weigh a preset amount of A1(NO3)3·9H2O and put it into a container, add a preset amount of C2H5OH into the container and stir until A1(NO3)3·9H2O is completely dissolved, and then pour the mixed solution into the reactor; S4: weighing Fe-Si-A1 powder of a preset particle size according to a preset formula, pouring the Fe-Si-A1 powder into the reaction kettle, and continuing to stir for 10 minutes; S5: adding a pH buffer solution to the reactor to adjust the pH of the mixed solution to 4, then placing the reactor in a 50° C. water bath and heating and stirring for 4 h, and then filtering, washing, and drying the material in the reactor; S6: The Fe-Si-A1 powder that has been preliminarily coated is sieved with a 200-mesh sieve and poured into a crucible, and then the crucible is placed in a tubular furnace for annealing. The atmosphere is an Ar inert gas. The maximum annealing temperature is set to 500°C, the heating rate is 5°C / min, and the crucible is cooled with the furnace; S7: The heat-treated Fe-Si-A1 powder is sieved with an 80-mesh sieve, and the sieve is added with 8% resin and 4% release agent and mixed evenly; S8: using a compression molding process, placing the mixture into a mold of a preset shape, and pressing it at a preset pressure to obtain an Fe-Si-Al powder core green body coated with alumina; S9: Load the pressed F-Si-A1 powder core green body into an annealing furnace. The annealing temperature is 730°C and the annealing time is 4 hours. The annealed powder core can be cooled in the furnace.

[0009] Specifically, in step S1 , the particle sizes of the Fe—Si—Al powders prepared by the gas atomization process are: D50=5 μm, D50=35 μm, and D50=90 μm, respectively.

[0010] Specifically, in step S2, the material ratio of the buffer solution is: 3-8 kg of Na2CO3 is added to every 100 L of deionized water.

[0011] Specifically, in step S3, the material ratio for preparing the aluminum source solution is: 2-12 kg of Al(NO3)3·9H2O is added to every 100 L of C2H5OH.

[0012] Specifically, in step S4, the ratio of the input amount of Fe-Si-A1 powder is: for every 100L of buffer solution prepared by deionized water and 100L of aluminum source solution prepared by C2H5OH put into the reactor, 55KG of Fe-Si-A1 powder needs to be put in.

[0013] Specifically, when the Fe-Si-A1 powder is insulated and coated, it can be passivated with phosphoric acid first, which mainly includes the following steps: S11: prepare a passivation solution, weigh a preset amount of phosphoric acid and put it into a container, add a preset amount of C3H60 into the container and stir to completely disperse the phosphoric acid; S12: weigh a preset amount of Fe-Si-A1 powder and put it into another container, stir it continuously to make the Fe-Si-A1 powder passivated evenly, then put the container into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the magnetic powder for 2 hours; S13: The dried powder is sieved with an 80-mesh sieve, and the sieved material is subjected to insulation coating treatment.

[0014] Specifically, in step S11, the material input ratio of the passivation solution is: 0.5 kg to 2.1 kg of phosphoric acid is required to be added to every 20 L of C3H60.

[0015] Specifically, in step S12, the input ratio of Fe-Si-A1 powder is: the mass of Fe-Si-A1 powder required to be input for preparing 20L of passivation solution is 100KG.

[0016] In summary, the present invention discloses a metal magnetic powder core APC atomized iron silicon aluminum production process. First, Fe-Si-A1 powders with particle sizes of D50=5μm, D50=35μm and D50=90μm are prepared by aerosol method; then, Fe-Si-A1 powders with small particle sizes are passivated by phosphoric acid; then, A1(OH)3 is prepared by aluminum ion hydrolysis method to preliminarily coat the magnetic powder, and then most of the A1(OH)3 on the surface of the magnetic powder is decomposed into aluminum oxide by heat treatment, thereby achieving the purpose of insulation coating; finally, the magnetic powder core is pressed and formed. Under medium and high frequency and large Bm value conditions, the use of small particle size powder can effectively reduce magnetic loss and increase the anti-saturation performance of the powder core; and in the powder core prepared by Fe-Si-A1 powder coated with aluminum oxide, the density and effective magnetic permeability of the powder core decrease with the increase of aluminum oxide dosage and increase with the increase of molding pressure. The DC bias performance increases with the increase of aluminum oxide dosage and decreases with the increase of molding pressure. The magnetic loss first decreases and then increases with the increase of the amount of alumina and the molding pressure. Therefore, the metal magnetic powder core APC gas atomization sendust production process of the present invention solves the technical problem of how to improve the soft magnetic properties of the gas atomization sendust soft magnetic powder core. DETAILED DESCRIPTION

[0017] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0018] Specifically, the present invention provides a metal magnetic powder core APC gas atomization FeSiAl production process, which comprises the following steps: S1: preparing Fe-Si-Al powder with a preset particle size by gas atomization process; S2: Prepare buffer solution, weigh a preset amount of Na2CO3 and deionized water, place in a container and mix and stir until the solution is clear; S3: Prepare an aluminum source solution, weigh a preset amount of A1(NO3)3·9H2O and put it into a container, add a preset amount of C2H5OH into the container and stir until A1(NO3)3·9H2O is completely dissolved, and then pour the mixed solution into the reactor; S4: weighing Fe-Si-A1 powder of a preset particle size according to a preset formula, pouring the Fe-Si-A1 powder into the reaction kettle, and continuing to stir for 10 minutes; S5: adding a pH buffer solution to the reactor to adjust the pH of the mixed solution to 4, then placing the reactor in a 50° C. water bath and heating and stirring for 4 h, and then filtering, washing, and drying the material in the reactor; S6: The Fe-Si-A1 powder that has been preliminarily coated is sieved with a 200-mesh sieve and poured into a crucible, and then the crucible is placed in a tubular furnace for annealing. The atmosphere is an Ar inert gas. The maximum annealing temperature is set to 500°C, the heating rate is 5°C / min, and the crucible is cooled with the furnace; S7: The heat-treated Fe-Si-A1 powder is sieved with an 80-mesh sieve, and the sieve is added with 8% resin and 4% release agent and mixed evenly; S8: using a compression molding process, placing the mixture into a mold of a preset shape, and pressing it at a preset pressure to obtain an Fe-Si-Al powder core green body coated with alumina; S9: Load the pressed F-Si-A1 powder core green body into an annealing furnace. The annealing temperature is 730°C and the annealing time is 4 hours. The annealed powder core can be cooled in the furnace.

[0019] Specifically, in the aforementioned step S1, the particle sizes of the Fe—Si—Al powders prepared by the gas atomization process are: D50=5 μm, D50=35 μm and D50=90 μm respectively.

[0020] Specifically, in the aforementioned step S2, the material ratio for preparing the buffer solution is: 3-8 kg of Na2CO3 is added to every 100 L of deionized water.

[0021] Specifically, in the aforementioned step S3, the material ratio for preparing the aluminum source solution is: 2-12 kg of A1(NO3)3·9H2O is added to every 100 L of C2H5OH.

[0022] Specifically, in the aforementioned step S4, the ratio of the input amount of Fe-Si-A1 powder is that for every 100L of buffer solution prepared by deionized water and 100L of aluminum source solution prepared by C2H5OH put into the reactor, 55KG of Fe-Si-A1 powder needs to be put in.

[0023] Specifically, in step S7, the release agent is C 36 H 70 O4Zn.

[0024] Furthermore, soft magnetic composite materials composed of various metal magnetic powders and insulating materials, namely SMC, have been widely used in power electronic equipment such as reactors and inverters. Compared with traditional soft magnetic materials such as silicon steel and ferrite, SMC has the advantages of low eddy current loss, high DC bias performance and high magnetic flux density. In order to further reduce the eddy current loss of SMC and improve the anti-saturation ability, most of the existing technologies have proposed different insulation methods to block the magnetic path between the eddy current path and the magnetic powder. However, with the increase in the frequency and power of electronic equipment, it has become more difficult to reduce medium and high frequency losses and improve anti-saturation ability by simply optimizing the insulation quality of the powder.

[0025] Therefore, the present invention proposes a method for optimizing the particle size of Fe-Si-A1 powder by atomization process to improve the soft magnetic properties of the powder core. The soft magnetic powder prepared by atomization method presents a regular spherical shape, is easy to coat, and has excellent coating layer integrity.

[0026] Specifically, when the Fe-Si-A1 powder is insulated and coated, it can be passivated with phosphoric acid first, which mainly includes the following steps: S11: prepare a passivation solution, weigh a preset amount of phosphoric acid and put it into a container, add a preset amount of C3H60 into the container and stir to completely disperse the phosphoric acid; S12: weigh a preset amount of Fe-Si-A1 powder and put it into another container, stir it continuously to make the Fe-Si-A1 powder passivated evenly, then put the container into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the magnetic powder for 2 hours; S13: The dried powder is sieved with an 80-mesh sieve, and the sieved material is subjected to insulation coating treatment.

[0027] Specifically, in the aforementioned step S11, the material input ratio of the passivation solution is: 0.5 kg to 2.1 kg of phosphoric acid is required to be added to every 20 L of C3H60.

[0028] Specifically, in the aforementioned step S12, the input ratio of Fe-Si-A1 powder is: the mass of Fe-Si-A1 powder to be input for preparing 20L of passivation solution is 100KG.

[0029] Specifically, the Fe-Si-A1 powder disclosed in the prior art usually has a particle size of D50=150μm and above, and is mainly prepared by mechanical grinding methods such as ball milling. The Fe-Si-A1 powder disclosed in the APC atomization iron silicon aluminum production process for a metal magnetic powder core of the present invention is prepared by atomization to achieve a particle size effect less than or equal to D50=90μm. Therefore, the resistivity of the magnetic powder core can be significantly improved, thereby limiting eddy currents and effectively reducing magnetic losses.

[0030] The resistivity test method of the magnetic powder core is as follows: First, apply a layer of silver paste evenly on the upper and lower surfaces of the soft magnetic powder core and dry it at 60°C for 30 minutes; then, clamp two thin copper plates on the upper and lower surfaces of the magnetic powder core and connect them to the intelligent DC resistance tester to measure the volume resistance, R. Finally, calculate the volume resistivity of the magnetic powder core, p, according to formula 1, where l and S are the height and cross-sectional area of ​​the powder core respectively: Formula 1: R = pl / s Therefore, the comparative sample 1 prepared by the Fe-Si-A1 powder with a particle size of D50=150μm disclosed in the prior art can be compared with the embodiments 1-3 using the metal magnetic powder core APC atomization iron silicon aluminum production process of the present invention when the particle sizes of the Fe-Si-A1 powder are D50=5μm, D50=35μm and D50=90μm respectively, and the resistivity data are shown in Table 1 below.

[0031] Table 1: Comparative test data of resistivity

[0032] Specifically, combined with the data in Table 1, it can be seen that under medium and high frequency and high Bm conditions, small particle size Fe-Si-A1 powder helps to increase the resistivity of the magnetic powder core, thereby limiting eddy currents and effectively reducing magnetic losses. In addition, the powder core prepared from small particle size powder has a low effective magnetic permeability, but good DC bias performance can be obtained. The reason is that small particle size and low density bring about a large effective demagnetization field. When the magnetic permeability is adjusted to the same, due to the similar effective demagnetization field inside the powder core, the particle size has little effect on the anti-saturation ability and magnetic loss under low frequency and low Bm, but by reducing the particle size, the loss of the powder core under medium and high frequency and high Bm can still be greatly reduced.

[0033] In summary, the present invention discloses a metal magnetic powder core APC atomized iron silicon aluminum production process. First, Fe-Si-A1 powders with particle sizes of D50=5μm, D50=35μm and D50=90μm are prepared by aerosol method; then, Fe-Si-A1 powders with small particle sizes are passivated by phosphoric acid; then, A1(OH)3 is prepared by aluminum ion hydrolysis method to preliminarily coat the magnetic powder, and then most of the A1(OH)3 on the surface of the magnetic powder is decomposed into aluminum oxide by heat treatment, thereby achieving the purpose of insulation coating; finally, the magnetic powder core is pressed and formed. Under medium and high frequency and large Bm value conditions, the use of small particle size powder can effectively reduce magnetic loss and increase the anti-saturation performance of the powder core; and in the powder core prepared by Fe-Si-A1 powder coated with aluminum oxide, the density and effective magnetic permeability of the powder core decrease with the increase of aluminum oxide dosage and increase with the increase of molding pressure. The DC bias performance increases with the increase of aluminum oxide dosage and decreases with the increase of molding pressure. The magnetic loss first decreases and then increases with the increase of the amount of alumina and the molding pressure. Therefore, the metal magnetic powder core APC gas atomization sendust production process of the present invention solves the technical problem of how to improve the soft magnetic properties of the gas atomization sendust soft magnetic powder core.

[0034] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0035] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A metal magnetic powder core APC gas atomization FeSiAl production process, characterized in that: It includes the following steps: S1: preparing Fe-Si-Al powder with a preset particle size by gas atomization process; S2: Prepare buffer solution, weigh a preset amount of Na2CO3 and deionized water, place in a container and mix and stir until the solution is clear; S3: Prepare an aluminum source solution, weigh a preset amount of A1(NO3)3·9H2O and put it into a container, add a preset amount of C2H5OH into the container and stir until A1(NO3)3·9H2O is completely dissolved, and then pour the mixed solution into the reactor; S4: weighing Fe-Si-A1 powder of a preset particle size according to a preset formula, pouring the Fe-Si-A1 powder into the reaction kettle, and continuing to stir for 10 minutes; S5: adding a pH buffer solution to the reactor to adjust the pH of the mixed solution to 4, then placing the reactor in a 50° C. water bath and heating and stirring for 4 h, and then filtering, washing, and drying the material in the reactor; S6: The Fe-Si-A1 powder that has been preliminarily coated is sieved with a 200-mesh sieve and poured into a crucible, and then the crucible is placed in a tubular furnace for annealing. The atmosphere is an Ar inert gas. The maximum annealing temperature is set to 500°C, the heating rate is 5°C / min, and the crucible is cooled with the furnace; S7: The heat-treated Fe-Si-A1 powder is sieved with an 80-mesh sieve, and the sieve is added with 8% resin and 4% release agent and mixed evenly; S8: using a compression molding process, placing the mixture into a mold of a preset shape, and pressing it at a preset pressure to obtain an Fe-Si-Al powder core green body coated with alumina; S9: Load the pressed F-Si-A1 powder core green body into an annealing furnace. The annealing temperature is 730°C and the annealing time is 4 hours. The annealed powder core can be cooled in the furnace.

2. A metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S1 , the particle sizes of Fe—Si—Al powders prepared by gas atomization process are: D50=5 μm, D50=35 μm and D50=90 μm respectively.

3. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S2, the material ratio of the buffer solution is as follows: 3-8 kg of Na2CO3 is added to every 100 L of deionized water.

4. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S3, the material ratio for preparing the aluminum source solution is: 2-12 kg of Al(NO3)3·9H2O is added for every 100 L of C2H5OH.

5. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S4, the ratio of the input amount of Fe-Si-A1 powder is: for every 100L of buffer solution prepared by deionized water and 100L of aluminum source solution prepared by C2H5OH put into the reactor, 55KG of Fe-Si-A1 powder needs to be put in.

6. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: When the Fe-Si-A1 powder is insulated and coated, it can be passivated with phosphoric acid first, which mainly includes the following steps: S11: prepare a passivation solution, weigh a preset amount of phosphoric acid and put it into a container, add a preset amount of C3H60 into the container and stir to completely disperse the phosphoric acid; S12: weigh a preset amount of Fe-Si-A1 powder and put it into another container, stir it continuously to make the Fe-Si-A1 powder passivated evenly, then put the container into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the magnetic powder for 2 hours; S13: The dried powder is sieved with an 80-mesh sieve, and the sieved material is subjected to insulation coating treatment.

7. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S11, the material input ratio of the passivation solution is: 0.5KG to 2.1KG of phosphoric acid is required for every 20L of C3H60.

8. The metal magnetic powder core APC gas atomization sendust production process according to claim 1, characterized in that: In step S12, the input ratio of Fe-Si-A1 powder is: the mass of Fe-Si-A1 powder required to be input for preparing 20L of passivation solution is 100KG.

Citation Information

Patent Citations

  • A method for preparing a high-permeability gas-atomized iron-silicon-aluminum magnetic powder core

    CN109285685B

  • A method for preparing gas-atomized iron-silicon-aluminum powder

    CN109317688B

  • Power coating method of metal soft magnetic composite and preparing method of metal soft magnetic composite

    CN104368807A

  • Iron-silicon-aluminum magnetic powder core and preparation method thereof

    CN105931790A

  • Low-loss soft magnetic powder core and preparation method thereof

    CN111370193A